A NeutroStructure-Driven Approach to Elderly Care Community Planning and Design Under the Background of Rural Revitalization - Xianqin Yan; Yuanpei Zhou; Rong Fang (Neutrosophic Sets and Systems)
This study introduces a new planning model called the Plithogenic Dynamic NeutroStructure (PDNS) to help design elderly care communities in rural areas. The model is based on NeutroStructure theory [1], where not all rules or facts or ideas are completely true or false. Instead, they are partly true, partly uncertain, and partly false. This is more realistic for real-life situations, especially in rural planning, where many things are not clear or fixed. The PDNS model uses expert opinions to evaluate different locations based on four key factors: accessibility, cost, environmental sustainability, and community support. Each factor is measured using three values: how true it is (T), how uncertain it is (I), and how false it is (F). The model also allows these values to change over time, making it flexible and dynamic. A case study was done with five possible sites in a rural area. The results showed that PDNS helped identify the best site by carefully balancing the different factors, even when the information was unclear or conflicting. Compared to traditional models, PDNS gives more accurate, flexible, and realistic results. This makes it a strong tool for planning elderly care services in rural communities.